2015
DOI: 10.1530/erc-14-0502
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CLAUDIN-1 on follicular thyroid carcinoma aggressiveness

Abstract: CLAUDIN-1 belongs to the family of transmembrane tight junction proteins tightening the paracellular cleft of epithelial cells. In human malignancies, CLAUDIN-1 is often dysregulated and located in subcellular compartments, particularly in the nucleus where it may influence cellular behaviour. Here, we studied CLAUDIN-1 in relation to the biological characteristics of follicular thyroid carcinoma (FTC). CLAUDIN-1 immuno-staining showed loss of membrane expression and increased nuclear CLAUDIN-1 localization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…Tzelepi et al demonstrated reduced expression of claudin-1, -4, and -7 in dedifferentiated thyroid carcinomas [14]. A recent study demonstrated that increased nuclear claudin-1 expression in FTC cell lines correlated with increased tumor cell motility, invasion, and metastasis which were potentially related to protein kinase C activity [9]. In the current cohort of 90 PTCs, no nuclear claudin-1 staining was noted in any tumors.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Tzelepi et al demonstrated reduced expression of claudin-1, -4, and -7 in dedifferentiated thyroid carcinomas [14]. A recent study demonstrated that increased nuclear claudin-1 expression in FTC cell lines correlated with increased tumor cell motility, invasion, and metastasis which were potentially related to protein kinase C activity [9]. In the current cohort of 90 PTCs, no nuclear claudin-1 staining was noted in any tumors.…”
Section: Discussionmentioning
confidence: 41%
“…While several cellular mechanisms interacting with various players of cell signaling pathways regulate tumor cell invasiveness, altered expression of the tight junction integral molecules has been linked to the pathogenesis of malignant tumors. Claudins, which are one of the integral molecules of tight junctions maintaining the integrity of the cell polarity and barrier function, have also been linked to cell dysadhesion, increased cell motility, epithelial mesenchymal transition, cell proliferation as well as metastatic potential [6][7][8][9]. While one can except that downregulation of these molecules can result in loss of cell polarity and cell invasiveness, recent evidence suggests that both up and downregulation of claudins bear a biologic significance in a tumor-and claudin-specific manner [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLDN11 is a member of the claudin protein family and is a critical component of tight junctions, where it serves a key role in regulating cell junctions and cell adhesion (28). Previous results have indicated that CLDN11 may suppress the proliferation, invasion and apoptosis of many tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Although claudins are members of the tetraspanin family of proteins, which are integral to the structure and function of TJs, changes in the cellular localization of claudins serve an important role during tumorigenesis (19). Previous studies reported that the expression of claudin-1 increased in human colon cancers with mislocalization from the cell membrane to the nucleus and cytoplasm (19), the predominant cytoplasmic and nuclear localization of claudin-1 reduced apoptosis in nasopharyngeal carcinoma cells (28), and claudin-1 showed loss of membrane expression and increased nuclear localization in follicular thyroid carcinoma (39). The cytoplasmic expression of claudin-1 in metastatic melanoma cells was also shown to be critical for increased malignancy (27,40).…”
Section: Discussionmentioning
confidence: 99%